A Federal Perspective on the Abkhaz-Georgian Conflict : From Intractability to Pacification. - Gurashi, Romina (Cambridge Scholars Publishing, 2017)
Since the beginning of the 21st century, the problem of the development of regional security has become increasingly relevant in international politics. Of particular concern is the post-Soviet space, which remains in the most difficult process of transformation. The Georgian-Abkhaz conflict, which entered a sharp phase in 1992, was one of the first and most lengthy (1992-2008) international conflicts in the former Soviet Union. Complex factors, such as the deep roots of the confrontation, the great human sacrifices of the political parties during the hostilities, the high degree of defensive.